Intraocular Pressure Response to Maximal Exercise Test during Recovery - Najmanova, Eliska; Pluhacek, Frantisek; Botek, Michal (Optometry and vision science, 2018)
SIGNIFICANCE: The main aim of this study was to determine the intraocular pressure (IOP) response to maximal incremental running test during 30 minutes of recovery. Exhaustive exercise induced a highly individually variable IOP response, which was related to its initial value and the initial heart rate. PURPOSE: The purpose of the study was to analyzed the IOP response to a maximal incremental running test in healthy women during a 30-minute recovery period. Secondarily, the study attempted to determine if the IOP was dependent on its baseline, maximal oxygen uptake, initial heart rate, and autonomic nervous system regulation. METHODS: Twenty-four healthy women between the ages of 19 and 30 years were recruited for the study. Initial IOP (baseline), heart rate, and autonomic nervous system regulation were measured after 30 minutes of rest. Each subject then underwent an incremental running test on a treadmill to reach the maximal physical activity and to determine physical fitness based on maximal oxygen uptake. Intraocular pressure and autonomic nervous system activity were measured immediately after completion of the physical activity during a 30-minute recovery period in the supine position. RESULTS: The IOP variability increased markedly after the exercise up to 1.7-fold of the resting state. The IOP before and after exercise did not differ significantly; however, the lower baseline revealed a significant increase in comparison with the higher baseline. The time course of the IOP changes was significantly influenced by the initial heart rate. All other effects, interactions, and correlations were insignificant. CONCLUSIONS: The IOP response after maximal exercise was highly dependent on the individual. The IOP seems to be slightly increasing with a significant dependence on its resting baseline and initial heart rate.
Keywords: Exercise Test; Tonometry, Ocular; spotřeba kyslíku; Oxygen Consumption; Intraocular Pressure; obnova funkce; nitrooční tlak; Running; Adult; mladý dospělý; tonometrie oční; Heart Rate; srdeční frekvence; Young Adult; ženské pohlaví; Recovery of Function; Humans; zátěžový test; dospělí; běh; Female; lidé